Connexins and Pannexins: New Insights into Microglial Functions and Dysfunctions - Gajardo-Gómez, Rosario; Labra, Valeria C.; Orellana, Juan A. (Frontiers in Molecular Neuroscience, 2016)
Under physiological conditions, microglia adopt a resting phenotype associated with the production of anti-inflammatory and neurotrophic factors. In response to a wide variety of insults, these cells shift to an activated phenotype that is necessary for the proper restoration of brain homeostasis. However, when the intensity of a threat is relatively high, microglial activation worsens the progression of damage rather than providing protection, with potentially significant consequences for neuronal survival. Coordinated interactions among microglia and other brain cells, including astrocytes and neurons, are critical for the development of timely and optimal inflammatory responses in the brain parenchyma. Tissue synchronization is in part mediated by connexins and pannexins, which are protein families that form different plasma membrane channels to communicate with neighboring cells. Gap junction channels (which are exclusively formed by connexins in vertebrates) connect the cytoplasm of contacting cells to coordinate electrical and metabolic coupling. Hemichannels (HCs) and pannexons (which are formed by connexins and pannexins, respectively) communicate the intra- and extracellular compartments and serve as diffusion pathways for the exchange of ions and small molecules. In this review article, we discuss the available evidence concerning the functional expression and regulation of connexin- and pannexin-based channels in microglia and their contributions to microglial function and dysfunction. Specifically, we focus on the possible implications of these channels in microglia-to-microglia, microglia-to-astrocyte and neuron-to-microglia interactions in the inflamed brain.